Cover Image. (18th November 2018) - Vrkoslav, Vladimír; Muck, Alexander; Brown, Jeffery M.; Hubálek, Martin; Cvačka, Josef
Abstract : The front cover image is based on the Research Article The MALDI In‐Source Decay of Peptides Using Ion Mobility Enabled Quadrupole‐Time‐of‐Flight Mass Spectrometry by Vladimír Vrkoslav et al., https://doi.org/10.1002/rcm.8284 . Illustration Credit: Tomáš Belloň/IN2ON.